Effects of strength training, detraining and retraining in muscle strength, hypertrophy and functional tasks in older female adults - Correa, Cleiton S.; Cunha, Giovani; Marques, Nise [UNESP]; Oliveira-Reischak, Alvaro; Pinto, Ronei (Wiley-Blackwell, 2016)
Introduction: Previous studies presented different results regarding the maintenance time of muscular adaptations after strength training and the ability to resume the gains on muscular performance after resumption of the training programme. Objective: This study aimed to verify the effect of strength training on knee extensors and elbow flexor muscle strength, rectus femoris muscle volume and functional performance in older female adults after 12 weeks of strength training, 1 year of detraining and followed by 12 weeks of retraining. Methods: Twelve sedentary older women performed 12 weeks of strength training, 1 year of detraining and 12 weeks of retraining. The strength training was performed twice a week, and the assessment was made four times: at the baseline, after the strength training, after the detraining and after the retraining. The knee extensor and elbow flexor strength, rectus femoris muscle volume and functional task were assessed. Results: Strength of knee extensor and elbow flexor muscles, rectus femoris muscle volume and 30-s sit-to-stand increased from baseline to post-training (respectively, 40%, 70%, 38% and 46%), decreased after detraining (respectively, -36%, -64%, - 35% and -43%) and increased again these parameters after retraining (35%, 68%, 36% and 42%). Conclusion: Strength training induces gains on strength and hypertrophy, also increased the performance on functional tasks after the strength training. The stoppage of the strength caused strength loss and reduction of functional performance. The resumption of the strength training promoted the same gains of muscular performance in older female adults.
Keywords: ageing; dynapenia; muscle weakness; muscular atrophy